2013
DOI: 10.1088/0957-4484/25/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and sensing in plexcitonic nanocavities: from simple molecular linkers to molecular aggregate layers

Abstract: We present a theoretical study of a metal-molecular aggregate hybrid system consisting of a strongly coupled dimer connected by molecules characterized by an excitonic transition. The plasmonic resonances of the metallic dimer interact with the molecular excitations giving rise to coupled plasmon-exciton states, so called plexcitons. We compare the differences in the optical response when the excitonic material is placed only as a linker in the plasmonic gap of the dimer and when the material is distributed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…1(b) we also present the solutions obtained through two different analytic approaches: solid red circles represent the hybrid mode frequencies obtained from the CHO model, while open triangles correspond to analytic solutions based on Mie theory -both are in excellent agreement with the full simulations. Due to its simplicity, the oscillator model is frequently adopted in literature to describe the modes in strongly-coupled plexcitonic geometries [7,42,45]. In the general case, the (complex) energies of the two hybrid modes are given by [1,16]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(b) we also present the solutions obtained through two different analytic approaches: solid red circles represent the hybrid mode frequencies obtained from the CHO model, while open triangles correspond to analytic solutions based on Mie theory -both are in excellent agreement with the full simulations. Due to its simplicity, the oscillator model is frequently adopted in literature to describe the modes in strongly-coupled plexcitonic geometries [7,42,45]. In the general case, the (complex) energies of the two hybrid modes are given by [1,16]…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of excitons with plasmons is usually traced through the Rabi splitting in optical spectra [4,11], but recent elaborate experiments showed that it is also possible to observe the coherent energy exchange between the optical states of the two components in real time through the corresponding Rabi oscillations [37][38][39]. Tailoring the plasmonic environment is gradually departing from the regime of single nanoparticles [12,13,40,41], and dimers [42][43][44][45][46][47][48] or nanoparticle arrays [49][50][51][52][53] are exploited to benefit from their stronger field confinement and enhancement. A similar coupling has also been observed for the interaction of emitters with the phononic modes of SiC antennae [54], while engineering the electromagnetic vacuum through evanescent plasmon modes was recently proposed as a promising route towards increased light-matter interactions [55].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding eigenvalues are E p , E 1 , E 2 , E 3 and E 4 , respectively. Then, the five-branched anticrossing can be obtained by diagonalizing the Hamiltonian, which can be written as, 40,48,54,[67][68][69]…”
Section: (A) Seven Representative Extinction Curves Of Thementioning
confidence: 99%
“…22 At zero detuning, the energy separation between the upper and lower polariton branches representing the strength of the coupling is called Rabi splitting energy, ћΩ=2g where g stands for the coupling constant indicating the degree of the strong coupling. Until now, many studies on plasmon-exciton hybrid nanoparticles focused on plasmonic nanostructures with a variety of shapes, 23 e.g., core-shell nanoparticles, 20 nanoprisms, hollow gold nanoprism, 24 nanorods, nanoparticle dimers, 25 nanorings, 7 and recently nanodisks. 13 However, in order to boost plasmon-exciton interaction at nanoscale dimension and expand the application of plexcitonic nanoparticles in a variety of fields such as solar cells, 26 light emitting diodes, and nanolasers, new plexcitonic nanoparticles with outstanding optical and chemical properties remains a key goal and challenge.…”
Section: Introductionmentioning
confidence: 99%